(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2025)
Climate change is rapidly emerging as one of the most significant drivers of biodiversity loss, yet wildlife conservation policy frameworks – designed primarily to address habitat loss, overexploitation, and invasive species – have been slow to integrate climate adaptation objectives into statutory planning instruments, protected area management plans, and species recovery programmes. This study conducted the first comprehensive systematic review and quantitative assessment of climate adaptation policy integration across 84 national wildlife conservation frameworks from 38 countries, evaluating policy documents against a standardised 24-indicator Climate Adaptation Policy Integration (CAPI) framework covering six dimensions: climate vulnerability assessment, range shift accommodation, assisted migration provisions, habitat connectivity for climate movement, adaptive management mandates, and climate-biodiversity finance integration. Mean CAPI score across all 84 frameworks was 3.84 +- 1.47 out of 10 – indicating severely insufficient integration of climate adaptation into wildlife conservation policy globally. Only 12 of 84 frameworks (14.3%) achieved CAPI scores > 6.0 (adequate integration). Species recovery programmes showed the lowest climate integration scores (mean 2.84 +- 1.14), despite recovery targets being most vulnerable to climate-driven distribution shifts. Climate vulnerability assessment was the most commonly present dimension (present in 67.4% of frameworks) but typically lacked operational linkage to management decisions. Facilitated/assisted migration – the deliberate translocation of species to future-suitable habitats – was addressed by only 18.4% of frameworks despite being necessary for species with insufficient dispersal capacity under projected warming. Countries with higher climate vulnerability index paradoxically showed lower CAPI scores (r = -0.34, p < 0.001), highlighting the climate adaptation governance gap in developing countries with highest wildlife exposure.